Self analysis - "Hubbard, L.Ron" (Copenhagen, 2007)
The book starts with an introduction of basic concepts of how the mind works and what it takes to improve its performance. Secondly it contains a chart which is very helpful in predicting the behavior of others (i.e. who can you trust or not), and it contains a number of processes which you can do with yourself to improve memory and well-being. Using this book, through a series of light yet powerful processes applied for as little as half an hour a day for two weeks, an individual on his own can come to a markedly improved outlook on life. This is where positive thinking becomes a reality. It is quite easy to do and shows results quite fast.